2014
DOI: 10.1254/jphs.13244fp
|View full text |Cite
|
Sign up to set email alerts
|

Goshajinkigan, a Traditional Japanese Medicine, Prevents Oxaliplatin-Induced Acute Peripheral Neuropathy by Suppressing Functional Alteration of TRP Channels in Rat

Abstract: Abstract. The acute peripheral neuropathy induced by oxaliplatin treatment occurs very frequently and is aggravated by exposure to cold. Goshajinkigan (GJG), a traditional Japanese (kampo) medicine, was recently shown to be effective against oxaliplatin-induced acute neuropathy. However, because the effects of GJG and its mechanism in relation to those of its ingredients and its mechanism are not well understood, we examined the effects of GJG on acute neuropathy. Further, we investigated whether GJG affects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 40 publications
(43 reference statements)
1
45
0
Order By: Relevance
“…In the present study, oxaliplatin caused cold and mechanical allodynia in the early phase, consistent with previous reports [10,17,31]. The repeated application of LLLT reduced the oxaliplatin-induced cold and mechanical allodynic responses in the von Frey test, acetone test, cold-water (5°C) limbimmersion test, as well as menthol-evoked nocifensive behavior in rats.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, oxaliplatin caused cold and mechanical allodynia in the early phase, consistent with previous reports [10,17,31]. The repeated application of LLLT reduced the oxaliplatin-induced cold and mechanical allodynic responses in the von Frey test, acetone test, cold-water (5°C) limbimmersion test, as well as menthol-evoked nocifensive behavior in rats.…”
Section: Discussionsupporting
confidence: 93%
“…Accumulating evidence from recent studies indicates that TRPM8, which is activated by cooling temperatures and agents such as menthol, is responsible for oxaliplatininduced cold hypersensitivity [9,10,31,38]. In this study, based on Western blot results, administration of oxaliplatin increased the protein levels of TRPM8 in DRG.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…An increasing number of studies report the involvement of TRP channels including TRPA1, TRPM8, TRPV1, and TRPV4 in CIPN [112][113][114][115]. Recent studies found that Jesengsingi-Hwan prevents oxaliplatin-induced peripheral neuropathy through the functional alteration in TRPA1 and TRPM8 [116] and can reduce paclitaxel-induced peripheral neuropathy by suppressing TRPV4 expression [117]. Moreover, the TRPV1-mediated anti-cancer effects of cannabidiol have been reported in multiple cancer cell lines, including breast [118], lung [119,120], and colon [121].…”
Section: Discussionmentioning
confidence: 99%